Biomechanics of a plant-derived sealant for corneal injuries - Liu, Betty; Liao, Matthew; Wagner, Willi Linus; Khalil, Hassan A.; Chen, Zi; Ackermann, Maximilian; Mentzer, Steven J. (Translational Vision Science & Technology, 2023)
The corneal epithelium has a glycocalyx composed of membrane-associated glycoproteins, mucins, and galactin-3. Similar to the glycocalyx in visceral tissues, the corneal glycocalyx functions to limit fluid loss and minimize frictional forces. Recently, the plant-derived heteropolysaccharide pectin has been shown to physically entangle with the visceral organ glycocalyx. The ability of pectin to entangle with the corneal epithelium is unknown. To explore the potential role of pectin as a corneal bioadhesive, we assessed the adhesive characteristics of pectin films in a bovine globe model. Pectin film was flexible, translucent, and low profile (80 µm thick). Molded in tape form, pectin films were significantly more adherent to the bovine cornea than control biopolymers of nanocellulose fibers, sodium hyaluronate, and carboxymethyl cellulose (P < 0.05). Adhesion strength was near maximal within seconds of contact. Compatible with wound closure under tension, the relative adhesion strength was greatest at a peel angle less than 45 degrees. The - corneal incisions sealed with pectin film were resistant to anterior chamber pressure fluctuations ranging from negative 51.3 ± 8.9 mm Hg to positive 214 ± 68.6 mm Hg. Consistent with these findings, scanning electron microscopy demonstrated a low-profile film densely adherent to the bovine cornea. Finally, the adhesion of the pectin films facilitated the en face harvest of the corneal epithelium without physical dissection or enzymatic digestion. We conclude that pectin films strongly adhere to the corneal glycocalyx. The plant-derived pectin biopolymer provides potential utility for corneal wound healing as well as targeted drug delivery.